The political power of business : structure and information in public policymaking - Bernhagen, Patrick (Trinity College (Dublin, Ireland). Department of Political Science, 2005)
In this study, I analyse the conditions that lead to the political power position of business in democratic capitalist systems. Overcoming traditional dichotomies of structural economic determinants versus corporate political action, I investigate how in their political strategies business lobbyists employ privately held information about the costs and effects of public policy in the real world. I argue that business' privileged access to policy-relevant information is an important power resource alongside more commonly researched resources such as money and organisation, membership in elite networks, or the prerogative over allocation and investment. In a review of the main theoretical strands of scholarly work on business and politics: (neo-) pluralist group theory, network approaches, theories of ideological domination, and structural power theories - I evaluate the main contributions that these approaches make to explaining the sources and limits of business political power.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin